Identifikasi Infeksi Multidrug Resistant Organism (MDRO) pada Pasien ICU - Sifira Kristiningrum; Ika Yuni Widyawati; Nuh Huda (Journal of Telenursing (JOTING), 2023)
This study aims to determine the clinical significance of Multidrug-Resistant Organism (MDRO) screening and analysis of infection risk factors in the intensive care unit (ICU). The method used is a descriptive design with a cross-sectional approach. The results showed that the majority of MDRO patients in the ICU were aged 36-45 years in the late adult age category by 45% and were found in the Central ICU by 63% with a length of stay of 1-15 days by 62 found by taking sputum specimens (47% ). Identification of the most Gram-negative bacteria in the ICU: Klebsiella pneumoniae ESBL, Escherichia Coli ESBL, Pseudomonas aeruginosa, and Acinetobacter Baummannii. Five bacteria are in the Multidrug Resistant Organism (MDRO) category: Klebsiella pneumoniae ESBL, Escherichia Coli ESBL, Pseudomonas aeruginosa, Acinetobacter Baummannii, and MRSA. In conclusion, a high MDRO infection will be at risk of transmission to other patients. So early detection is needed in all patients who will undergo treatment at the hospital. Keywords: Antibiotics, Bacteria, ICU, Infection, Multidrug-Resistant Organisms